Perception, Attitude and Impact Change after Watching Faith-Based Films: A Comparative Study - Wok, Saodah; Abdul Manaf, Nor Faridah; Ismail, Rizalawati (2014)
Understanding each other’s religions and cultures are important for maintaining peace and harmony especially in Malaysia. Therefore, this study was conducted to analyze the impact of Islamic films or films related to Islam and Muslims on youth (teenagers, adolescents, and young adults) of various races, religions and gender. Specifically, the objectives of the study are to (1) to find out the level of perception on Islamic films among various youth backgrounds, (2) to find out the level of attitude towards Islamic films among various youth backgrounds, (3) to find out the level of impact change from watching Islamic films among various youth backgrounds, and (4) to analyze the relationships between impact change from watching Islamic films on attitude towards and perception on Islamic films for various youth backgrounds. The data were collected from an experimental research method, using questionnaire as the research instrument. From a total of 141 respondents, about two-thirds are females, 70% are teenagers representing different races and from different religions. Data were analyzed using SPSS WIN 17. Both descriptive statistics and inferential statistics were used to answer the objectives and hypotheses of the study. Results showed that there is no difference between males and females in terms of perception, attitude and impact change from watching Islamic films. However, the differences lie for perception, attitude, and impact change for the various race, religion, and age groups. Therefore, relevant authorities should take heed on how to ensure that the faith-based films are meaningful for the diverse youth to treasure staying in Malaysia so that unity is attained despite the diversity in their backgrounds.